2019
DOI: 10.18502/ijm.v11i1.701
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of virulence factors and biofilm formation in Pseudomonas aeruginosa obtained from different clinical specimens in Bandar Abbas

Abstract: Background and Objectives: Pseudomonas aeruginosa is a ubiquitous opportunistic pathogen. The presence of several virulence factors such as exotoxin and exoenzyme genes and biofilm may contribute to its pathogenicity. The purpose of this study was to investigate the presence of toxA, exoU and exoS, the determination of biofilm production and antimicrobial susceptibility patterns among clinical isolates of P. aeruginosa. Materials and Methods: In this study, 75 isolates of P. aeruginosa were recovered fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 13 publications
4
22
1
1
Order By: Relevance
“…In addition, it needs for bacterial dissemination during infection (Yousefi-Avarvand et al, 2015). Our results identified exoS gene most prevalent (70%) within the P. aeruginosa isolates which in agreement with other study and similar to (Bahador et al, 2019, Mingxiang et al, 2018. In Poland, Pobiega revealed a rate for exoS (92.3%) among clinical samples (Amirmozafari et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, it needs for bacterial dissemination during infection (Yousefi-Avarvand et al, 2015). Our results identified exoS gene most prevalent (70%) within the P. aeruginosa isolates which in agreement with other study and similar to (Bahador et al, 2019, Mingxiang et al, 2018. In Poland, Pobiega revealed a rate for exoS (92.3%) among clinical samples (Amirmozafari et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…The current study identified that (98%, 85%) of the isolated samples produced biofilm by TCP and CRP method respectively, this is agreed with (Jabalameli et al, 2012, Hamad, 2018. The biofilm production facilitates to ascent bacterial resistant strains and eases the efficacy of antibiotic therapy (Bahador et al, 2019). ExoS is a major cytotoxin that is required for bacterial colonisation and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…We used a quantitative phenotypic test considered to be a gold standard to detect biofilm production by clinical isolates of P. aeruginosa. Moreover, different studies that used the same technique to analyze biofilm production by P. aeruginosa obtained percentages for biofilm production ranging from 73.7 % to 98.6 % in the isolates analyzed 1 , 3 , 6 , 9 , 10 , 24 , that were higher than those described in this study.…”
Section: Discussioncontrasting
confidence: 64%
“…Pseudomonas aeruginosa , as a non-fermenter gram-negative bacterium can survive under various environmental conditions. It is an opportunistic pathogen that can colonize in healthy individuals and moist sites in the hospitals ( 1 ). This bacterium causes a wide range of infections, particularly in immunocompromised, burn, and cystic fibrosis patients.…”
Section: Introductionmentioning
confidence: 99%